Linking selective chemical extraction of iron oxyhydroxides to arsenic bioaccessibility in soil. (December 2015) - Palumbo-Roe, Barbara; Wragg, Joanna; Cave, Mark
Abstract: The relationship between As bioaccessibility using the physiologically based extraction test (PBET) and As extracted by hydroxylamine hydrochloride (HH), targeting the dissolution of amorphous Fe oxyhydroxides, is established in soils from the British Geological Survey Geochemical Baseline Survey of SW England, UK, to represent low As background and high As mineralised/mined soils. The HH-extracted As was of the same order of magnitude as the As extracted in the bioaccessibility test and proved to be a better estimate of bioaccessible As than total As (bioaccessible As − total As: r = 0.955; bioaccessible As – HH-extracted As: r = 0.974; p-values = 0.000). These results provide a means of estimating soil As bioaccessibility on the basis of the HH extraction. Further selective extraction data, using hydrochloride acid that seeks to dissolve both amorphous and crystalline Fe oxyhydroxides, indicates a decrease in the As bioaccessible fraction with the increase of the soil Fe oxyhydroxide crystallinity. Highlights: Approach identified the source of bioaccessible As as amorphous Fe oxyhydroxides. Estimation of soil bound As bioaccessibility using a hydroxylamine hydrochloride extraction. Decreases in As bioaccessibility related to increases in crystallinity of soil Fe. Abstract : Arsenic extracted by hydroxylamine hydrochloride, a soil extraction method targeting the dissolution of amorphous Fe oxyhydroxides, provides a close estimate of oral bioaccessible As.